Analysis of the Health Related Quality of Life Elderly People Living in Rural Areas - Mirczak, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
In connection with the aging of the population and the increase in the number of people with chronic illnesses, the priority objective for health care has become not only lengthening life, but also improving quality of life in older persons, as well as maintenance of their relative independence and active participation in social life. The most important factor in determining quality of life is health. Therefore, within this concept is used the term ‘health related quality of life’ which means quality of life designated state of health, current illnesses and the natural ageing process. The main goal of the present study was to investigate the health related quality of life of elderly people living in rural areas and to identify its determinants. The group of respondents consisted 203 people aged 65 years and over living in rural areas in Małopolska. The analysis of collected research material was performed using the statistical package SPSS 19 for Windows. The level of significance for the tested the hypotheses assumed value of 0.05. Elderly people who living in rural areas showed lower health related quality of life in physical dimension than in psychological dimension. The factors that determined this assessment including: sex, age, family situation, housing and financial situation, agricultural work in the past, health status, functional state, the risk of malnutrition, the type of the support and the level of life satisfaction of respondents.